Intestinal Barrier Dysfunction and Microbial Translocation in Human Immunodeficiency Virus–Infected Pregnant Women Are Associated With Preterm Birth. (24th March 2018) - Shivakoti, Rupak; Gupte, Nikhil; Kumar, Nathella Pavan; Kulkarni, Vandana; Balasubramanian, Usha; Bhosale, Ramesh; Sambrey, Pradeep; Kinikar, Aarti; Bharadwaj, Renu; Patil, Sandesh; Inamdar, Sadaf; Suryavanshi, Nishi; et al.
Abstract : In our study of HIV-1–infected pregnant women, those with higher levels of markers for monocyte activation and intestinal integrity dysfunction during pregnancy had an increased odds of preterm delivery. Interventions targeting gut integrity and microbial translocation may help reduce preterm birth. Abstract: Background: Preterm birth (PTB) rates are high in human immunodeficiency virus (HIV)–infected populations, even when on treatment. Still, only a subset of all births in HIV-infected pregnant women result in PTB, suggesting that risk factors other than HIV infection itself are also important. Inflammation is a known risk factor in uninfected populations, but its role in HIV-infected population have not been studied; in addition, the immune pathways involved are not clear and noninvasive immune markers with predictive value are lacking. Our objective was to determine the association of select markers of inflammation with PTB in HIV-1–infected pregnant women. Methods: Within a randomized trial of pregnant women receiving nevirapine (Six-Week Extended-Dose Nevirapine [SWEN] trial), we nested a case-control study (n = 107; 26 cases, 81 controls) to determine the association of maternal inflammation with PTB. Cases were defined as PTB (<37 weeks' gestational age). We assessed inflammation by measuring plasma levels of markers of general inflammation (C-reactive protein [CRP]), intestinal barrier dysfunction (intestinal fatty acid binding protein [I-FABP]), and microbial translocation/monocyte activation (soluble CD14 [sCD14] and CD163 [sCD163]). Multivariable logistic regression was used to determine the odds of PTB per log2 increase of each marker. Results: In multivariable models, there was increased odds of PTB per unit increase of log2 sCD14 (adjusted odds ratio [aOR], 2.45; 95% confidence interval [CI], 1.24–4.86), log2 sCD163 (aOR, 3.87; 95% CI, 1.43–10.49), and log2 I-FABP (aOR, 2.28; 95% CI, 1.18–4.41) but not log2 CRP (aOR, 0.72; 95% CI, .48–1.09). Conclusions: Our results show that select immune markers can identify women at higher risk for PTB in HIV-1–infected populations and suggest that modulating gut barrier integrity and microbial translocation may affect PTB. Clinical Trials Registration: NCT00061321.